Haemophagocytic lymphohistiocytosis as a complication of combination anti-PD-1 and anti-CTLA-4 checkpoint inhibitor immunotherapy for metastatic melanoma, and the outcome of rechallenge with single-agent anti-PD-1 immunotherapy. Issue 8 (10th August 2022) - Holmes, Zachary; Courtney, Ashling; Hiong, Alison
Abstract : A woman with metastatic melanoma was treated with immunotherapy induction with ipilimumab and nivolumab and radiotherapy to liver metastases. The patient deteriorated shortly thereafter, becoming febrile and hypotensive and requiring admission to the intensie care unit (ICU) for inotrope support. Failure to respond to antibiotics and a negative septic screen prompted further investigation, which ultimately led to a diagnosis of haemophagocytic lymphohistiocytosis (HLH). The patient improved on high dose steroids and was discharged home. Months later, in the context of progressive melanoma, the patient was re-challenged with nivolumab monotherapy and subsequently experienced recurrence of HLH, confirming the aetiology as being immunotherapy related. This case serves as a reminder to consider HLH where there are fevers of unknown origin in an unwell patient receiving immune checkpoint inhibitor therapy and also highlights immunotherapy as a potential cause for HLH, which has rarely been reported in the literature to date.